A light-absorbing-modified CBN grinding wheel and preparation method thereof

By adding toner coating to the CBN grinding wheel abrasive layer, the characteristics of micro-blasting and micro-cladding clusters during laser shaping and sharpening processes are used to solve the problems of uneven heat distribution and large energy loss during laser trimming, and the efficient and good quality grinding wheel trimming effect is achieved.

CN119681806BActive Publication Date: 2025-04-18HUNAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510206312.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-18
Estimated Expiration
2045-02-25

AI Technical Summary

Technical Problem

During the laser trimming process, the heat distribution on the surface of the CBN grinding wheel is uneven, resulting in uneven thermal stress, affecting the overall strength and service duration of the grinding wheel, and the laser energy loss is large, which limits the improvement of dressing quality and efficiency.

Method used

A light-absorbing-modified CBN grinding wheel is used, and abrasive layer is added to the material of the abrasive layer, including micro-blasting clusters and micro-clad clusters. Through the thermal response of micro-blasting clusters and the melting flow of micro-clad clusters during laser shaping and sharpening, laser energy is evenly distributed, reducing thermal damage and improving trimming efficiency.

Benefits of technology

It significantly improves the efficiency and quality of laser trimming, reduces the loss of laser energy, extends the service time of the grinding wheel, and improves the overall performance of the grinding wheel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681806B_ABST
    Figure CN119681806B_ABST
Patent Text Reader

Abstract

The present invention discloses a light-absorbing modified CBN grinding wheel and a preparation method thereof. The grinding wheel is prepared by the following method: (1) crushing and sieving CBN abrasive grains; (2) forming a metal coating on the surface of micro-crushed CBN abrasive grains; (3) configuring a CBN grinding wheel abrasive layer material, wherein the CBN grinding wheel abrasive layer material includes micro-crushed CBN abrasive grains and a carbon powder coating group; (4) filling the CBN grinding wheel abrasive layer material into a mold for mold pressing and curing; and (5) performing laser trimming. The light-absorbing modified CBN grinding wheel of the present invention is designed for the existing laser trimming process and has the advantages of high trimming efficiency, low energy loss and good performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of CBN (cubic boron nitride) grinding wheels, and in particular to a light-absorbing-modified CBN grinding wheel which is suitable for a laser dressing process, has high dressing efficiency, low energy consumption and good performance, and a preparation method thereof. Background Art

[0002] Superabrasive grinding wheels can be widely used in the grinding process of various hard, brittle, tough and difficult-to-process materials due to their stable physical and chemical properties, superior grinding performance and outstanding wear resistance. During the installation and use of superabrasive grinding wheels, the grinding wheel may become blunt or the circular runout may be too large, which requires further dressing to ensure the accuracy of the grinding wheel. However, due to the extremely high hardness of superabrasive grinding wheels, there are great difficulties in their processing and dressing.

[0003] Laser dressing is a non-contact processing method that selectively removes abrasive particles and binders by focusing a laser beam to achieve the required size and profile accuracy of the grinding wheel during installation and use, thereby avoiding the existence of mechanical forces and the loss of dressing tools during the dressing process. In theory, laser dressing can be applied to the dressing of various types of super-hard abrasive grinding wheels such as complex curved surface forming grinding wheels, ultra-thin grinding wheel cutting discs, parallel grinding wheels, etc. It is an advanced processing technology for the precision dressing of super-hard abrasive grinding wheels. However, when the laser is irradiated to the surface of the CBN grinding wheel, due to the differences in the thermophysical properties of the abrasive layer material (such as thermal conductivity, absorbance, specific heat capacity, etc.), the heat is unevenly distributed on the surface of the grinding wheel, causing the local temperature to be too high. The contact surface between the laser beam and the grinding wheel presents a large temperature difference, which leads to uneven distribution of thermal stress, seriously affecting the overall strength and service life of the grinding wheel. The combination of the above factors leads to a large amount of laser energy radiated on the surface of the grinding wheel being lost in vain, which seriously limits the improvement of laser dressing in terms of quality and efficiency.

[0004] In order to improve the quality and efficiency of laser dressing, the prior art generally improves the laser dressing device from the mechanism of laser ablation of the abrasive layer to overcome the disadvantages of thermal damage to the grinding wheel or unsatisfactory dressing effect. For example, the Chinese invention patents with publication numbers CN108555780A and CN117207073A have improved the grinding wheel laser dressing device, using online control system monitoring or grinding force signals to identify the grinding wheel state, and then adjusting the output power of the laser, the pulse frequency and duty cycle of the laser, and dressing the grinding wheel to the optimal state through real-time positive feedback during the dressing process. However, the device designed in the above patents fails to fully consider the geometric path of the pulsed laser on the surface of the grinding wheel and the evolution behavior of the abrasive layer material during the laser dressing process. It is difficult to formulate a suitable abrasive layer formulation scheme based on the thermophysical properties of the abrasive particles and binder materials in the abrasive layer to solve the current technical problems of improving the large laser energy loss and uneven temperature rise of the irradiated surface during the laser dressing process. Summary of the invention

[0005] The present invention provides a light-absorbing-modified CBN grinding wheel and a preparation method thereof, which are used to solve the technical problems of improving large laser energy loss and uneven temperature rise of the irradiated surface during laser finishing in the prior art mentioned in the background technology.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A method for preparing a light-absorbing-modified CBN grinding wheel comprises the following steps:

[0008] (1) crushing and sieving the CBN abrasive to obtain micro-crushed CBN abrasive;

[0009] (2) forming a metal coating on the surface of the micro-crushed CBN abrasive grains to obtain nickel-plated micro-crushed CBN abrasive grains;

[0010] (3) configuring a CBN grinding wheel abrasive layer material, wherein the CBN grinding wheel abrasive layer material includes the nickel-plated micro-crushed CBN abrasive grains and carbon powder coated agglomerates; the carbon powder coated agglomerates include at least one of micro-explosion agglomerates and micro-cladding agglomerates, and both the micro-explosion agglomerates and micro-cladding agglomerates are structures in which a carbon powder coated layer covers a core material, the core material of the micro-explosion agglomerates is energetic material particles, and the core material of the micro-cladding agglomerates is nickel-based alloy particles;

[0011] (4) filling the CBN grinding wheel abrasive layer material into a mold for molding and curing to obtain a light-absorbing-modified CBN grinding wheel embryo;

[0012] (5) The light-absorbing-modified CBN grinding wheel blank is subjected to laser trimming to obtain the light-absorbing-modified CBN grinding wheel.

[0013] The design idea of ​​the above technical solution is that, in view of the existing laser dressing process, the present invention specifically adds carbon powder coating groups to the abrasive layer material of the CBN grinding wheel. The micro-explosion agglomerates and micro-cladding agglomerates have different core materials, which produce corresponding effects in different dressing stages: in the laser shaping stage, the energetic material as the core material of the micro-explosion agglomerates will produce a rapid thermal response and release a certain amount of energy. The transient local temperature rise caused by absorbing laser energy will inevitably lead to thermal expansion of the material, thereby causing stress and strain, and stimulating elastic waves, thereby greatly removing the abrasive layer material in the area to be removed, and disrupting the plasma flow field of the abrasive layer during the ablation process, reducing the shielding effect of the laser, thereby improving the dressing efficiency. At the same time, this will also cause the internal cracks of the abrasive particles to connect with each other, thereby aggravating the local crushing of the abrasive particles and the loss of the abrasive particle volume, which is helpful to form a new cutting edge, thereby improving the sharpness of the abrasive particles. In the laser sharpening stage, the nickel-based alloy as the core material of the micro-cladding agglomerates will melt in the local area and then flow and spread rapidly. The molten nickel-based alloy can form a "thermal bridge" effect, which enables the laser energy to form a more uniform temperature gradient on the abrasive surface and the binder interface through efficient heat conduction, avoiding excessive concentration and uneven distribution of laser energy. Moreover, the molten and resolidified nickel-based alloy can fill the microcracks and irregular areas on the abrasive surface during the flow and spreading process, further enhancing the bonding stability between the abrasive and the binder.

[0014] As a further preferred embodiment of the above technical solution, in step (2), the preparation method of the micro-explosion agglomerates and micro-cladding agglomerates is as follows: after uniformly mixing the carbon powder and the carbon powder binder solution, the mixture is divided into a carbon powder mixture A and a carbon powder mixture B for standby use; energetic material particles and nickel-based alloy particles as core materials are added to the carbon powder mixture A and the carbon powder mixture B respectively, so that the surfaces of the energetic material particles and the nickel-based alloy particles are uniformly coated with the carbon powder particles to achieve carbon powder coating of the core material; the mixture is allowed to stand for drying and sieved to obtain the micro-explosion agglomerates and micro-cladding agglomerates.

[0015] As a further preferred embodiment of the above technical solution, the mass of the carbon powder binder is 50% to 70% of the mass of the carbon powder. The carbon powder binder includes the following components by mass: 30 to 45 parts of acrylic emulsion, 7 to 10 parts of polyvinyl alcohol, 4 to 8 parts of polycaprolactone, 5 to 9 parts of sodium dodecylbenzene sulfonate, 2 to 4 parts of ethylene glycol, 1 to 1.5 parts of dimethyl carbonate, 1 to 1.5 parts of furazolidone and 40 to 55 parts of water. The adhesion layer composed of carbon powder and carbon powder binder can effectively improve the photothermal conversion efficiency, and has a positive effect on improving the surface roughness of the core material, adjusting the reflectivity and uniform heat transfer.

[0016] As a further preferred embodiment of the above technical solution, when the average particle size of the CBN abrasive is 120 μm, the particle size of the energetic material particles is 30-50 μm, the particle size of the nickel-based alloy particles is 75-90 μm, and the particle size of the carbon powder is 30-90 nm.

[0017] As a further preferred embodiment of the above technical solution, the average diameter of the micro-explosion agglomerates in the carbon powder coated agglomerates is d 微爆破 The average particle size of abrasive particles d CBN 0.25~0.5, the average diameter of micro-cladding clusters d 微熔覆 The average particle size of abrasive particles d CBN 0.5~0.8, that is, the particle size of the carbon powder coated group and the particle size of the CBN abrasive grains satisfy the following relationship:

[0018] ;

[0019] In the formula, the diameter of micro-explosion cluster is d 微爆破 , the diameter of micro-cladding cluster is d 微熔覆 , the diameter coefficient of micro-explosion clusters is ξ , the diameter coefficient of micro-cladding clusters is δ The average particle size of CBN abrasive is d CBN .

[0020] The purpose of micro-explosion agglomeration is to improve the removal efficiency of the binder during laser dressing, destroy the shielding effect of the plasma layer and the vapor cloud, and use the shock wave to induce the abrasive to form an additional cutting edge. In order to avoid the abrasive particles from being broken into macroscopic pieces due to excessive blasting impact, the diameter of the micro-explosion agglomeration is limited to 0.25~0.5 of the abrasive particle diameter. The purpose of micro-cladding agglomeration is to melt the nickel-based alloy particles on the surface of the grinding wheel through a high-energy laser beam. The flow and spread of the molten material can alleviate the local uneven heating, and after solidification, the holding force of the binder on the abrasive particles and the wear resistance of the abrasive particle surface are enhanced. In order to ensure that there is sufficient cladding material on the surface of the grinding wheel to strengthen the bonding strength of the abrasive / binder and not affect the normal cutting operation of the abrasive particles, the diameter of the micro-explosion agglomeration is limited to 0.5~0.8 of the abrasive particle diameter.

[0021] As a further preferred embodiment of the above technical solution, the energetic material particles include at least one of FOX-7 (1,1-diamino-2,2-dinitroethylene) and LLM105 (2,6-diamino-3,5-dinitropyrazine-1-oxide); the nickel-based alloy particles include at least one of nickel-iron alloy and nickel-chromium alloy.

[0022] As a further preferred embodiment of the above technical solution, in step (1), the CBN abrasive is subjected to micro-crushing treatment, and the specific operation is as follows: placing the abrasive of the light-absorbing modified CBN grinding wheel in an alcohol solution, using an ultrasonic instrument to micro-crush the abrasive of the light-absorbing modified CBN grinding wheel, setting the ultrasonic excitation frequency, and continuously using ultrasonic high-frequency simple harmonic vibration to excite the CBN abrasive, so that the CBN abrasive is subjected to the excitation force and then causes forced vibration, so as to achieve the purpose of micro-crushing; setting the ratio of the ultrasonic excitation frequency to the natural frequency of the abrasive γ Between 0.8 and 1.25. The vibration frequency applied to the CBN abrasive is positively correlated with the damage of the CBN abrasive. By setting the ultrasonic excitation frequency and using ultrasonic high-frequency simple harmonic vibration to excite the CBN abrasive, the CBN abrasive is subjected to the excitation force and forced to vibrate. Under the action of ultrasonic vibration, the stress wave instantaneously generated inside the CBN abrasive will exceed the strength threshold of the abrasive, thereby achieving the effect of micro-crushing. The damage to the abrasive during ultrasonic crushing can be divided into three stages: microcrack initiation, stabilization, and penetration. With the accumulation of microstructural damage inside the abrasive, the CBN abrasive further undergoes macroscopic fracture and crushing under ultrasonic vibration. In order to maintain the damage of the abrasive in a local micro-crushing state, the ratio of the ultrasonic excitation frequency to the natural frequency of the abrasive is set. γ Between 0.8-1.25. After micro-crushing, during laser trimming, the light entering the CBN abrasive grains is difficult to penetrate the bottom coating of the abrasive grains. The interlaced micro-cracks inside the abrasive grains cause the light to be trapped in the micron structure and undergo multiple internal reflections. This phenomenon effectively reduces the loss of laser energy and improves the utilization efficiency of the laser inside the abrasive grains.

[0023] As a further preferred embodiment of the above technical solution, the metal coating in step (2) is a nickel metal coating, and the metal coating is formed on the surface of the micro-crushed CBN abrasive grains by electroplating. Nickel can provide good wear and corrosion protection, and the nickel layer has fine crystals and high bonding strength, so it can be used as a coating metal for the abrasive grains, effectively improving the wear resistance of the abrasive grains.

[0024] As a further preferred embodiment of the above technical solution, when the micro-crushed CBN abrasive grains are subjected to an electroplating process, a surfactant is added to the plating solution as a sanding agent.

[0025] As a further preferred embodiment of the above technical solution, the surfactant is a polyethylene glycol type nonionic surfactant and / or a quaternary ammonium salt type cationic surfactant, wherein the polyethylene glycol type nonionic surfactant includes at least one of polyethylene glycol, fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether; the quaternary ammonium salt type cationic surfactant includes at least one of dodecylamine hydrochloride, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and dodecylpyridinium chloride, etc. The surfactant can help the surface of the CBN abrasive to form a velvet structure metal plating layer similar to silk thread during the electroplating process. Since the velvet has a light trapping effect, the light propagation path during laser ablation is changed through the fine velvet structure, so that the incident laser is reflected and refracted multiple times on the surface of the abrasive, so that more laser energy is absorbed and converted into heat energy, and the reflectivity of the abrasive surface can be reduced to below 10%, thereby improving the light-to-heat conversion efficiency of the CBN abrasive surface.

[0026] As a further preferred embodiment of the above technical solution, the plating solution includes components with the following concentrations: 450~500g / L nickel sulfate, 30~50g / L nickel chloride, 30~50g / L boric acid, 3~5g / L sodium hydroxide, 0.1~5mg / L polyethylene glycol type nonionic surfactant and 0.5~5mg / L quaternary ammonium salt type cationic surfactant.

[0027] As a further preferred embodiment of the above technical solution, before electroplating, the micro-crushed CBN abrasive is roughened and coated with graphene as a conductive layer. The roughening operation is: boil the micro-crushed CBN abrasive with dilute HNO3 for 20 minutes, and then wash it with distilled water 2 to 3 times. On the one hand, the graphene conductive layer can simplify the electroplating process of non-conductive abrasives, provide a good conductive basis for the electroplating process, so that the abrasives can deposit anode materials more evenly during the electroplating process, and realize direct surface electroplating. On the other hand, graphene has excellent optical absorption performance and thermal conductivity, which can not only improve the absorption efficiency of laser energy, but also improve the thermal stability of abrasives, evenly disperse heat, reduce local overheating to reduce thermal stress and thermal damage, thereby improving the stability and precision of material processing. Roughening can increase the adhesion of the graphene conductive layer and the metal plating layer to the substrate.

[0028] As a further preferred embodiment of the above technical solution, in step (3), the CBN grinding wheel abrasive layer material includes the following components in parts by weight: 40 to 60 parts of nickel-plated micro-crushed CBN abrasive particles, 20 to 40 parts of resin binder, 5 to 10 parts of light absorber, 5 to 10 parts of carbon powder coated agglomerates and 10 to 15 parts of pore-forming agent.

[0029] As a further preferred embodiment of the above technical solution, in step (3), the resin binder is a phenolic resin, the light absorber is a Clear-weld light absorber (a near-infrared light absorber), and the pore-forming agent is a hollow alumina sphere. The Clear-weld light absorber has a good absorption effect on near-infrared lasers (800-1100nm), which can improve the laser removal efficiency of abrasives and binders on the grinding wheel surface, improve the subsequent grinding wheel dressing efficiency, and save laser dressing costs. The light absorber and carbon powder coating on the grinding wheel surface can maximize the interaction efficiency between the laser and the binder, which not only helps to prevent excessive scattering of laser energy, but also effectively controls the laser removal process of the binder by optimizing heat conduction and heat distribution. By reducing the waste of ineffective scattering and reflection of laser energy, the maximum utilization of the laser dressing effect can be achieved. This helps to ensure that the abrasive is in the best working state, thereby achieving ideal sharpness and cutting performance. The pore-forming agent is hollow alumina balls, which have controllable particle size and uniform shape. They can accurately control the size and distribution of pores in the grinding wheel, which is beneficial to adjusting the packing density of abrasive grains and resin binders, and can improve the self-sharpening and chip holding capacity of the grinding wheel.

[0030] As a further preferred embodiment of the above technical solution, in step (5), the laser dressing operation includes laser shaping and laser sharpening; during the laser shaping process, by making the laser power density reach the ablation threshold of the CBN grinding wheel, the tip of the abrasive grain is slightly broken to form a sharp grinding edge, and the abrasive grains and the binder are removed at the same time; during the laser sharpening process, by controlling the laser power between the binder ablation threshold and the CBN grinding wheel ablation threshold, the excess binder between the CBN abrasive grains is removed, so that a certain chip accommodating space is provided, and the CBN abrasive grains are protruded outside the binder, so that an ideal abrasive grain height is obtained to form a cutting edge.

[0031] Based on the same technical concept, the present invention also provides a light-absorbing-modified CBN grinding wheel, which is prepared by the preparation method described in the above technical solution.

[0032] Compared with the prior art, the CBN grinding wheel prepared by the special method of the present invention has the following beneficial effects compared with the prior art:

[0033] (1) High dressing efficiency. Compared with conventional superabrasive grinding wheels, the present invention formulates a suitable grinding wheel abrasive layer material formulation scheme based on the temperature rise characteristics of the grinding wheel abrasive layer during laser ablation, which helps to improve the uneven temperature rise and severe thermal damage on the surface of the superabrasive grinding wheel caused by laser radiation, significantly improves the dressing accuracy and efficiency, and is conducive to controlling the cost of laser dressing of grinding wheels.

[0034] (2) Low energy loss. The present invention utilizes methods such as micro-crushing of the internal abrasive particles, suede coating, and improved abrasive layer formulation to achieve good anti-reflection effects on light of different wavelengths. On this basis, a binder material group is further constructed to combine a high-efficiency finishing component with a high-light-absorbing component. By adjusting the superposition effect and component proportion of materials with different optical properties, the energy distribution of the transmitted laser is regulated, the loss of the incident light during output is reduced, and the light-to-heat conversion efficiency during the finishing process is enhanced.

[0035] (3) Good grinding wheel performance. When preparing the grinding wheel of the present invention, the resin binder in the radiation area is removed during the laser ablation process, but the light absorber and cladding particles will remain in a molten state on the surface of the grinding wheel and quickly fill into the gap between the abrasive and the binder. After solidification, the abrasive and the binder can be more tightly bonded, effectively extending the service life of the grinding wheel. In addition, the microcracks inside the micro-crushed abrasive are connected or extended outward under the promotion of thermal stress, thereby aggravating the local crushing of the abrasive. This loss of abrasive volume helps to form a new cutting edge, ensuring that the abrasive is in the best cutting state. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0037] Figure 1 Schematic diagram of laser dressing of the light-absorbing-modified CBN grinding wheel of Example 1;

[0038] Figure 2 Schematic diagram of the coated micro-crushed CBN abrasive grains of Example 1;

[0039] Figure 3 is a schematic cross-sectional view of the carbon powder coated agglomerate (micro-explosion agglomerate) of Example 1;

[0040] Figure 4 is a schematic cross-sectional view of the carbon powder coated cluster (micro-coated cluster) of Example 1;

[0041] Figure 5 The mixing flow chart of the light absorption-modified CBN grinding wheel abrasive layer material of Example 1;

[0042] Figure 6 Schematic diagram of the solidification of the light absorption-modified CBN grinding wheel blank of Example 1 in a mold. DETAILED DESCRIPTION

[0043] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0044] The present invention will be further described in detail below with reference to the accompanying drawings.

[0045] Embodiment 1:

[0046] This embodiment is based on the change of laser ablation strategy in the laser trimming process (the schematic diagram of laser trimming is shown in FIG. Figure 1 As shown in FIG. 1 ), a method for preparing a light-absorbing-modified CBN grinding wheel is proposed, comprising the following steps:

[0047] (1) Ultrasonic impact micro-crushing CBN abrasive to obtain micro-crushed CBN abrasive. Place the CBN abrasive in an alcohol solution and use an ultrasonic instrument to micro-crush the CBN abrasive. Place the ultrasonic impact crushed CBN abrasive in an oven for drying. Set the oven temperature to 145°C. When the temperature in the oven reaches the preset temperature, dry it for 15 hours and then sieve it through a filter to prevent finer abrasive debris from mixing into the material to obtain micro-crushed CBN abrasive. In this step, the average particle size of the CBN abrasive is d CBN The ratio of the ultrasonic excitation frequency to the natural frequency of the abrasive is set. γ , by continuously using ultrasonic high-frequency simple harmonic vibration to excite the CBN abrasive, so that it is subjected to the exciting force and then causes forced vibration, thereby achieving the expected micro-crushing effect inside the abrasive. The simple harmonic exciting force F on the CBN abrasive can be expressed as:

[0048] ;

[0049] Where, the amplitude of the abrasive particle displacement response is B , the stiffness coefficient of CBN abrasive is k The ratio of the external excitation frequency to the natural frequency of the abrasive is γ , the relative damping coefficient is λ When a large amplitude and high frequency impact the abrasive surface, the interior of the CBN abrasive will be subjected to an instantaneous force, which will induce internal microcracks. The ratio of the ultrasonic excitation frequency to the natural frequency of the abrasive γ is 0.95, and the impact time is 1min.

[0050] (2) Micro-crushed CBN abrasives are coated to obtain nickel-plated micro-crushed CBN abrasives. The micro-crushed CBN abrasives are boiled in dilute HNO3 for 20 minutes to roughen the surface of the micro-crushed CBN abrasives. The purpose of this process is to change the surface properties of the abrasives through chemical reactions, so that an irregular microstructure is formed on the surface to enhance the bonding between the coating and the abrasives. After roughening, the abrasives need to be washed with distilled water 2 to 3 times and dried to remove acidic substances and impurities that may remain on the surface. Then, a graphene layer is formed on the surface of the micro-crushed CBN abrasives by coating. Since graphene has excellent conductivity, it can simplify the electroplating process of the originally non-conductive CBN abrasives, realize direct electroplating on the surface of the CBN abrasives, and form a nickel metal coating13. In addition, coating the surface of the CBN abrasives with graphene not only helps to improve the bonding strength between the abrasives and the coating, but also can evenly transfer the heat generated by laser ablation, avoid local material damage caused by high temperature, and enhance the removal efficiency and processing stability of the abrasives during laser finishing.

[0051] Subsequently, the cathode plated part (micro-crushed CBN abrasive with a graphene layer) and the anode plate (nickel metal rod) are placed in the plating solution respectively. After the power supply is connected, the cathode and the anode are immersed in the plating solution, and together with the plating solution and the power supply, a complete electroplating circuit is formed. The plating solution includes: 460g / L nickel sulfate, 37g / L nickel chloride, 40g / L boric acid, 4g / L sodium hydroxide, 1.5mg / L polyethylene glycol, 0.3mg / L fatty alcohol polyoxyethylene ether, 1.5mg / L dodecyltrimethylammonium bromide, 0.35mg / L dodecyltrimethylammonium chloride, 1mg / L hexadecyltrimethylammonium bromide. The metallic nickel of the anode enters the plating solution in the form of ions through an oxidation reaction. When it contacts the cathode, a reduction reaction occurs, and the crystallized plating metal adheres to the surface of the plated part to form a nickel metal plating layer. The main reaction of nickel ions gaining electrons and reducing to metallic nickel occurs on the cathode, and the reaction formula is:

[0052] ;

[0053] There is also a side reaction of hydrogen ions being reduced to hydrogen gas, the reaction formula is:

[0054] ;

[0055] At the same time, the main reaction occurs on the anode where nickel loses electrons and undergoes oxidation to form nickel ions. The reaction formula is:

[0056] ;

[0057] In addition, there is an anode side reaction, namely the electrolysis of water, and the reaction formula is:

[0058] ;

[0059] Metal nickel continuously loses electrons at the anode and gains electrons at the cathode, passing through the plating solution in the form of ions from the anode to the cathode to form a nickel coating, thereby obtaining nickel-plated micro-crushed CBN abrasive grains. Before plating, the particle shape of the CBN abrasive grains is irregular and amber transparent. During the plating deposition process, a surfactant is added to the plating solution as a sanding agent to form a velvet structure similar to silk threads on the surface of the abrasive grains14. After plating, the surface of the CBN abrasive grains changes from amber transparent to non-transparent silver, accompanied by a metallic luster, and is densely covered with a velvet structure similar to silk threads. Because the velvet surface has a light-trapping effect, the reflectivity of the abrasive surface can be reduced to less than 10%, thereby improving the light-to-heat conversion efficiency of the CBN abrasive surface. Nickel-plated micro-crushed CBN abrasive grains such as Figure 2 As shown (in the figure, 11 is the surface of the micro-crushed CBN abrasive, 12 is the graphene layer, and 13 is the nickel metal plating layer).

[0060] (3) Preparation of carbon powder coated group. Carbon powder with an average particle size of 50 nm and a carbon powder binder solution with a carbon powder mass ratio of 65% (including the following components by mass: 34 parts of acrylic emulsion, 7 parts of polyvinyl alcohol, 5 parts of polycaprolactone, 5.8 parts of sodium dodecylbenzene sulfonate, 2.2 parts of ethylene glycol, 1.3 parts of dimethyl carbonate, 1 part of furazolidone, and 43.7 parts of water) were mixed together and put into a blender. After stirring at a speed of 2500 rpm at room temperature, the mixture was taken out for use.

[0061] Energetic material particles (1,1-diamino-2,2-dinitroethylene) with a particle size of 40μm and nickel-based alloy particles (Ni-3) with a particle size of 80μm were selected as the core materials of micro-explosion agglomerates and micro-cladding agglomerates, respectively. The energetic material particles and nickel-based alloy particles were sprinkled into the carbon powder mixture, and a vibrator was used to evenly coat the surface of the energetic material particle core and the nickel-based alloy particles with carbon powder particles to form a carbon powder adhesion layer, which effectively avoids the problems of uneven particle adhesion and particle agglomeration. The carbon powder coated agglomerates after coating were left to dry at room temperature for 30 hours and sieved with a filter to ensure the content and particle size uniformity of the carbon powder coated agglomerates, that is, the carbon powder coated agglomerates (micro-explosion agglomerates and micro-cladding agglomerates, the cross-sectional structures of the two are as shown in the figure) were obtained. Figure 3 and Figure 4 As shown, Figure 3 21 is a micro-explosion agglomerate, 23 is a micro-explosion agglomerate core material, Figure 4 22 is a micro-clad agglomerate, 24 is a micro-clad agglomerate core material, and 25 is a carbon powder adhesion layer).

[0062] Average particle size of carbon powder coated groups and abrasive particles with different functions d CBN The following relationship exists:

[0063] ;

[0064] In the formula, the diameter of micro-explosion cluster is d 微爆破 , the diameter of micro-cladding cluster is d 微熔覆 , the diameter coefficient of micro-explosion clusters is ξ , the diameter coefficient of micro-cladding clusters is δ .

[0065] (4) Preparation of light-absorbing modified CBN grinding wheel abrasive layer components. The mass percentage of each component in the light-absorbing modified CBN grinding wheel abrasive is: 50% coated micro-crushed CBN abrasive, 30% resin binder (phenolic resin), 5% light absorber (Clear-weld light absorber), 5% carbon powder coated agglomerates (micro-explosion agglomerates and micro-cladding agglomerates), and 10% pore-forming agent (alumina hollow spheres). Figure 5 As shown, the components are mixed in sequence, the nickel-plated micro-crushed CBN abrasive and the wetting agent are placed in a high-power mixer for stirring, the wetting agent is liquid phenolic resin, and the liquid phenolic resin can make the abrasive surface adhere to the binder more evenly, ensuring that the nickel-plated micro-crushed CBN abrasive in the abrasive layer has a strong holding force, and its component proportion is added to the resin binder; the coated micro-crushed CBN abrasive (mixed with the wetting agent), light absorber, pore-forming agent, carbon powder coated group and resin binder weighed according to the component ratio are stirred in the same direction for 2 to 3 hours in a high-power mixer, and then the obtained light-absorbing modified CBN grinding wheel abrasive is sieved and left to stand. The resin binder is phenolic resin, the light absorber is Clear-weld light absorber, and the pore-forming agent is hollow alumina sphere.

[0066] (5) The light-absorbing modified CBN grinding wheel is molded and solidified to obtain a light-absorbing-modified CBN grinding wheel embryo. Figure 6 As shown ( Figure 6 In the figure, 3 is a mold, 31 is a positioning cylinder, 32 is a mold cover, 4 is a CBN grinding wheel abrasive layer material, 5 is a grinding wheel base, 51 is a through hole, and 52 is an abrasive layer contact surface). In order to make the grinding wheel base and the abrasive layer fit more stably, the grinding wheel abrasive layer material and the grinding wheel base are cured and assembled in the mold in advance. The grinding wheel base is in the shape of a ring, and a through hole is opened at the center of the circle to facilitate the assembly of the grinding wheel and the processing machine. The abrasive layer contact surface of the grinding wheel base is provided with a plurality of grooves with rectangular cross-sections, which helps the abrasive layer and the grinding wheel base to fit more stably. The grinding wheel base is cleaned with xylene, dried and left to stand for use. The mold is in the shape of a ring, and a positioning cylinder is provided at the center of the circle to cooperate with the through hole of the grinding wheel base. The grinding wheel base is placed in the mold in advance to ensure the firm combination of the grinding wheel abrasive layer material and the grinding wheel base, and complete the preliminary grinding wheel curing. Then, the mold was tightened and covered with a mold cover, and placed in a constant pressure electric oven at (17-20)×10 5The grinding wheel is finally solidified by hot pressing at a pressure of 100 Pa and a temperature of 108°C. The material is taken out after cooling to room temperature in the furnace, thereby obtaining an untrimmed light-absorbing-modified CBN grinding wheel embryo.

[0067] (6) Laser dressing of light-absorbing-modified CBN grinding wheel. The laser shaping and laser sharpening of the light-absorbing-modified CBN grinding wheel blank are carried out in sequence. During the laser dressing process, the interaction between the laser and the grinding wheel surface should satisfy the following relationship:

[0068] ;

[0069] In the formula, the total laser energy acting on the surface of the material is E 总 , the laser energy reflected by the abrasive surface is E 反 , the laser energy absorbed by the abrasive surface is E 吸 , the laser energy transmitted through the abrasive surface is E 透 The average laser power is P , the laser repetition frequency is f .

[0070] Laser shaping process: shaping refers to the process of cutting the grinding wheel to slightly break the tip of the abrasive grain to form a sharp grinding edge. By increasing the laser power density to reach the ablation threshold of the abrasive layer of the grinding wheel, the abrasive grains and binder are removed at the same time.

[0071] As the laser ablation time increases, the abrasive coating is gradually removed, and the transparent material of the CBN abrasive itself gradually appears. Since the penetration depth of the laser in the coating is small, far less than the thickness of the coating, the nanosecond pulse laser beam that is shot into the coating-fragmented CBN abrasive is difficult to penetrate the bottom coating of the abrasive. The interlaced microcracks inside the abrasive trap the light in the micron structure and cause multiple internal reflections, so that the laser energy that penetrates into the abrasive can be completely absorbed, that is, E 透 = 0. This phenomenon effectively reduces the loss of laser energy and improves the utilization efficiency of the laser inside the abrasive. Assuming that the nanosecond pulse laser beam is incident on the abrasive surface at a normal angle, the reflectivity at each reflection is r . Light Reflection M The total reflectivity after R Total reflectivity R It can be expressed as:

[0072] ;

[0073] Total Absorption Rate A It can be expressed as:

[0074] ;

[0075] Inside the material, the intensity of the laser decays exponentially with the propagation distance, so the intensity of the laser at a distance z from the material surface can be expressed as:

[0076] ;

[0077] Where I(0) is the laser intensity on the material surface, is the absorption coefficient of the coated micro-fragmented CBN abrasive to the incident laser. The multiple internal reflections and the absorption of the internal broken structure work together to improve the abrasive absorption efficiency. When the pulsed laser irradiates the surface of the material, part of the pulsed laser will be reflected multiple times inside the coated micro-fragmented CBN abrasive, and the other part of the pulsed laser will be absorbed by the coated micro-fragmented CBN abrasive, resulting in local temperature rise. The absorbed energy is mainly related to the properties of the abrasive. In addition, the graphene coating plays an important auxiliary role. Graphene has excellent optical absorption properties and thermal conductivity, which can not only improve the absorption efficiency of laser energy, but also evenly disperse heat and reduce local overheating, thereby improving the stability and precision of material processing. When the energy exchange between the material itself and the outside world is not considered, and the energy absorbed by the material is completely converted into heat energy, its heat source Q (x, t) can be expressed as:

[0078] ;

[0079] In the formula, E 总 is the total laser energy, and the laser energy absorption rate of the abrasive layer material surface is A(T) The laser action point is x 0, the rise time of the pulse laser is t , the distribution functions of the line source laser in space and time are f ( x-x 0) and g(t) .

[0080] The laser energy can instantly heat and melt the surface layer of the grinding wheel in the ablation area and vaporize it in a very short time. The laser continues to provide energy. At this time, the binder vapor is still strongly heated, and the vaporization effect becomes more intense. At the same time, high-temperature plasma appears, and the generated plasma shock wave will be ejected along the incident direction of the laser beam. The plasma layer and the vapor cloud will seriously hinder the radiation of the pulsed laser energy. However, the laser energy diffuses rapidly in the ablation area, transferring the heat evenly to the micro-explosion agglomerates. The core material of the micro-explosion agglomerate quickly absorbs the laser irradiation energy through the carbon powder adhesion layer, and quickly releases energy and stimulates shock waves due to high-energy reactions in a short time. This process causes the plasma core to decay and collapse, making it impossible for the vapor cloud to completely form a dense barrier, thereby reducing its obstruction to the subsequent laser energy transmission. At the same time, the shock wave and high temperature generated by the violent reaction of the micro-explosion agglomerates help to quickly peel or crush the surrounding abrasive layer material in the area to be removed. This process can effectively remove excess binder material covering the surface of the abrasive grains, while enabling the abrasive grains to form sharp grinding edges, thereby improving the sharpness of the abrasive grains without causing excessive damage to the abrasive grains themselves.

[0081] Laser sharpening process: Sharpening is the process of controlling the laser power between the binder ablation threshold and the abrasive ablation threshold, removing the excess binder between the abrasive particles, allowing them to have a certain chip space, and making the abrasive particles protrude from the binder to obtain the ideal abrasive height and form a cutting edge.

[0082] Since the laser input energy during the sharpening process is much smaller than the laser input energy during the shaping process, the laser radiation is absorbed by the Clear-weld light absorber and the carbon powder coating in the binder, which improves the laser removal efficiency of the binder. The laser energy during the sharpening process does not exceed the absorption threshold of the micro-explosion agglomerates, and the micro-explosion agglomerates on the surface of the abrasive layer are almost consumed during the shaping process, so the micro-explosion agglomerates during the sharpening process will not cause additional damage.

[0083] As the laser radiation is gradually absorbed by the Clear-weld light absorber and the carbon powder coating and converted into heat energy, the Clear-weld light absorber and the micro-cladding agglomerate adjacent to the radiation area are heated to melt. The core material of the micro-cladding agglomerate is made of nickel-based alloys such as nickel-iron alloy or nickel-chromium alloy, so that the light absorber particles and the micro-cladding agglomerate core material are quickly heated and melted, and then quickly cooled and solidified, thereby forming a re-solidified layer with excellent wear resistance, corrosion resistance, high temperature oxidation resistance, thermal fatigue resistance and other properties on the surface of the binder or in the contact gap between the abrasive particles and the binder, further eliminating defects such as large-scale cracks or pores on the surface of the abrasive layer. The surface cladding layer can be determined by the degree of cladding. θ , height ratio η And the abrasive holding force per unit area F As an evaluation indicator, there is the following relationship:

[0084] ;

[0085] In the formula, the cladding layer area on the grinding wheel surface is A r The surface area of ​​the grinding wheel is A g The thickness of the cladding layer per unit area is H r The average height of the abrasive grains per unit area is H g , the number of abrasive particles per unit area is n The total force on a single abrasive particle is f The chemical bonding stress of a single abrasive particle is σ 1. The mechanical bonding stress of a single abrasive particle is σ 2. The free micro-cladding agglomerate core material and the melt of the Clear-weld light absorber will quickly spread and flow on the surface of the grinding wheel, avoiding excessive heat accumulation in a specific area of ​​the grinding wheel and slowing down the local temperature rise on the surface of the grinding wheel. This process not only helps prevent the laser heating area from overheating, but also achieves a smooth transfer of laser radiation heat energy, significantly improving the stability and efficiency of the dressing effect.

[0086] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. The above are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a light-absorbing-modified CBN grinding wheel, characterized in that: The following steps are involved: (1) crushing and sieving the CBN abrasive to obtain micro-crushed CBN abrasive; (2) forming a metal coating on the surface of the micro-crushed CBN abrasive grains to obtain nickel-plated micro-crushed CBN abrasive grains; (3) configuring a CBN grinding wheel abrasive layer material, wherein the CBN grinding wheel abrasive layer material includes the nickel-plated micro-crushed CBN abrasive grains and carbon powder coated agglomerates; the carbon powder coated agglomerates include at least one of micro-explosion agglomerates and micro-cladding agglomerates, and both the micro-explosion agglomerates and micro-cladding agglomerates are structures in which a carbon powder coated layer covers a core material, the core material of the micro-explosion agglomerates is energetic material particles, and the core material of the micro-cladding agglomerates is nickel-based alloy particles; (4) filling the CBN grinding wheel abrasive layer material into a mold for molding and curing to obtain a light-absorbing-modified CBN grinding wheel embryo; (5) The light-absorbing-modified CBN grinding wheel blank is subjected to laser trimming to obtain the light-absorbing-modified CBN grinding wheel.

2. The method for preparing the light-absorbing-modified CBN grinding wheel according to claim 1, characterized in that: In step (2), the preparation method of the micro-explosion agglomerates and micro-cladding agglomerates is as follows: after uniformly mixing carbon powder and carbon powder binder solution, the mixture is divided into carbon powder mixture A and carbon powder mixture B for standby use; energetic material particles and nickel-based alloy particles as core materials are added to carbon powder mixture A and carbon powder mixture B respectively, so that the surfaces of energetic material particles and nickel-based alloy particles are uniformly coated with carbon powder particles to achieve carbon powder coating of the core material; the mixture is allowed to stand for drying and sieved to obtain the micro-explosion agglomerates and micro-cladding agglomerates.

3. The method for preparing the light-absorbing-modified CBN grinding wheel according to claim 2, characterized in that: The average diameter of the micro-explosion agglomerates in the carbon powder coated agglomerates is 0.25-0.5 of the average particle size of the abrasive particles, and the average diameter of the micro-cladding agglomerates is 0.5-0.8 of the average particle size of the abrasive particles.

4. The method for preparing the light-absorbing-modified CBN grinding wheel according to claim 2, characterized in that: The energetic material particles include at least one of FOX7 and LLM105; the nickel-based alloy particles include at least one of nickel-iron alloy and nickel-chromium alloy.

5. The method for preparing the light-absorbing-modified CBN grinding wheel according to any one of claims 1 to 4, characterized in that: In step (1), the CBN abrasive is subjected to micro-crushing treatment, and the specific operation is: placing the abrasive of the light-absorbing-modified CBN grinding wheel in an alcohol solution, using an ultrasonic instrument to micro-crush the abrasive of the light-absorbing-modified CBN grinding wheel; setting the ratio γ of the ultrasonic excitation frequency to the natural frequency of the abrasive to be between 0.8 and 1.

25.

6. The method for preparing the light-absorbing-modified CBN grinding wheel according to any one of claims 1 to 4, characterized in that: In step (2), the metal coating is a nickel metal coating, and the metal coating is formed on the surface of the micro-crushed CBN abrasive grains by an electroplating process; before electroplating, the micro-crushed CBN abrasive grains are roughened and coated with graphene as a conductive layer.

7. The method for preparing the light-absorbing-modified CBN grinding wheel according to claim 6, characterized in that: When the micro-crushed CBN abrasive grains are electroplated, a surfactant is added to the plating solution as a sanding agent; the surfactant is a polyethylene glycol type nonionic surfactant and / or a quaternary ammonium salt type cationic surfactant.

8. The method for preparing the light-absorbing-modified CBN grinding wheel according to any one of claims 1 to 4, characterized in that: In step (3), the CBN grinding wheel abrasive layer material includes the following components in parts by weight: 40-60 parts of nickel-plated micro-crushed CBN abrasive grains, 20-40 parts of resin binder, 5-10 parts of light absorber, 5-10 parts of carbon powder coated agglomerates and 10-15 parts of pore-forming agent.

9. The method for preparing the light-absorbing-modified CBN grinding wheel according to any one of claims 1 to 4, characterized in that: In step (5), the laser dressing operation includes laser shaping and laser sharpening. During the laser shaping process, by making the laser power density reach the ablation threshold of the CBN grinding wheel, the tip of the abrasive grain is slightly broken to form a sharp grinding edge, and at the same time, the abrasive layer material in the area to be removed from the grinding wheel blank is removed, and the profile error of the CBN grinding wheel is accurately trimmed. During the laser sharpening process, by controlling the laser power between the binder ablation threshold and the CBN grinding wheel ablation threshold, the excess binder between the CBN abrasive grains is removed, so that they have chip accommodating space, and the CBN abrasive grains are protruded outside the binder, so as to obtain an ideal abrasive grain height and form a cutting edge.

10. A light-absorbing-modified CBN grinding wheel, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Laser trimming system for grinding wheel

    CN108555780A

  • Diamond grinding wheel laser trimming device and method

    CN117207073A

  • Concave curve surface superhard grinding material grinding wheel laser trimming device and method

    CN103802039A

  • Conglomerate abrasive particles, abrasive articles including the same, and methods of making the same

    CN105813808A